Exudative Retinal Detachment: An Unusual Ocular Manifestation of Syphilis - Belfaiza Soukaina; Abdellaoui Taoufiq; Fiqhi Issam; Mouzari Yassine; Reda Karim; Oubaaz Abdel Bar (Indian Journal of Medical Specialities)
Ocular syphilis is a disease known as a great simulator. It can affect the structures of the eye. It often manifests by an anterior uveitis. Posterior segment involvement is very rare and it is exceptionally complicated by exudative retinal detachment. We report the case of a patient with bilateral bullous retinal detachment in the context of ocular syphilis with a good evolution after treatment by penicillin G and corticotherapy.